Environmental impact study by life cycle assessment of the use of alumina nanoparticles as an additive in biodiesel/diesel blends (2015)
(Eng) Life cycle assessment (LCA) considers the whole life cycle of a product or process, from the origin of the raw materials up to the final disposition of the wastes. In this work, LCA methodology was applied in the evaluation of the environmental impact that is caused by the use of alumina nanoparticles as an additive in biodiesel/diesel blends, considering the synthesis of the alumina nanoparticles through sol-gel method. SIMAPRO software (CML method) was used to evaluate the potential impacts of each stage of the process. Although the use of the nanoparticles caused a reduction in the emissions of CO2, SO2 and particulate material (PM); an increase in most of the impact categories (acidification, eutrophication and marine eco-toxicity) was observed during combustion. This can be attributed to the increasing emissions of NOx and the toxic effect related to the synthesis of the nanoparticles, when compared to combustion without nano-additive. These results indicated that there is a need to carry further research on the use of nanoadditives in biofuels, to verify the renewability of these alternatives regarding the sustainability of the process.